2018
DOI: 10.1038/s41598-018-31271-2
|View full text |Cite
|
Sign up to set email alerts
|

The double solid solution (Zr, Nb)2(Al, Sn)C MAX phase: a steric stability approach

Abstract: The addition of Nb and Sn to Zr2AlC is investigated, targeting the synthesis of a Zr-rich bulk MAX phase free of ZrC. The 211 phase formation in the two quaternary Zr-Nb-Al-C and Zr-Al-Sn-C systems is evaluated. Solubility over the entire compositional range in (Zr, Nb)2AlC and Zr2(Al, Sn)C is observed. In terms of effectiveness, the addition of Sn is preferred over the addition of Nb, as the former is selectively incorporated into the 211 structure. A combinatorial approach results in the formation of phase-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 38 publications
1
40
0
Order By: Relevance
“…1). In order to increase the amount of the 413 MAX phase, 50% of the Al content was substituted for Sn, in analogy with prior studies on the synthesis of phase-pure (Zr,Nb)2(Al,Sn)C [41] and (Zr,Ti)2(Al,Sn)C [20] MAX phase ceramics. In those studies, the enhanced stability of the 211 MAX phases over the competing binary phases (carbides, intermetallics) was associated with the trigonal prism distortion parameter and the relative size of the M and A atoms in the M6A prism [42].…”
Section: Effects Of Sn Additionmentioning
confidence: 99%
See 2 more Smart Citations
“…1). In order to increase the amount of the 413 MAX phase, 50% of the Al content was substituted for Sn, in analogy with prior studies on the synthesis of phase-pure (Zr,Nb)2(Al,Sn)C [41] and (Zr,Ti)2(Al,Sn)C [20] MAX phase ceramics. In those studies, the enhanced stability of the 211 MAX phases over the competing binary phases (carbides, intermetallics) was associated with the trigonal prism distortion parameter and the relative size of the M and A atoms in the M6A prism [42].…”
Section: Effects Of Sn Additionmentioning
confidence: 99%
“…These studies demonstrated experimentally that highly phase-pure bulk MAX phase ceramics can be produced by forming solid solutions on both M and A sites [42]. Apart from giving a comprehensive review of the importance of steric effects in MAX phase lattice distortions, one of these studies demonstrated that a reduced prismatic distortion in the crystal lattice due to smaller differences in the M and A atomic sizes could ensure the synthesis of phase-pure (Zr0.8,Nb0.2)2(Al0.5,Sn0.5)C MAX phase ceramics [41].…”
Section: Effects Of Sn Additionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that only in those MAX phases reported to react and to form solid solutions with Bi/Pb, the stress field around the Al atoms was in tension when compared to the natural state of fcc Al. [41] in the Zr2(Al,Bi,Pb)C MAX phase solid solution, using the NPD data acquired from the hot pressed Zr2(Al,Bi,Pb)C ceramic, results in a reduced trigonal prism distortion of 1.080 (Zr2AlC = 1.101 [42]) and an increased octahedral distortion of 1.1103 (Zr2AlC = 1.034 [42]). Recent studies showed that aiming to reduce the trigonal prism distortion by making double solid solution MAX phases (i.e., solid solutions on both M and A sites of the 'host' MAX phase compounds) enhanced the phase purity of the produced ceramics [42,73].…”
Section: The Chemical Instability Of Zr2alc In Liquid Lbementioning
confidence: 99%
“…Hence, In this study, Ti3SiC2 and Ti3AlC2 are investigated as potential structural materials to expose their further potential for technological and industrial applications as they are considered promising candidates for applications where materials are subjected to extreme environments, like nuclear reactors 1,3,13,14,20 . Therefore, comprehensive knowledge of their electronic, structural stabilities and elastic properties is crucial so that our results will resolve some inconsistency where they exist in the reported properties of these materials.…”
Section: Introductionmentioning
confidence: 99%